Are psoriasis and psoriatic arthritis associated with chronic obstructive pulmonary disease? - Agnieszka B. Owczarczyk-Saczonek; Jacek Owczarczyk; Magdalena Krajewska-Włodarczyk; Joanna Wojtkiewicz; Waldemar Placek (Termedia Publishing House, 2019)
Chronic obstructive pulmonary disease is a chronic inflammation affecting the peripheral airways and pulmonary parenchyma, leading to irreversible and progressive airflow limitation. In recent years attention has been paid to more frequent coexistence with psoriasis. Both diseases are provoked by similar factors, such as smoking, abdominal obesity, lack of physical activity, and concomitance with the metabolic syndrome. In addition, similarities in pathogenesis, regarding the roles of Th1 and Th17 can be found, resulting in an increase in the proinflammatory cytokines levels. Both in psoriasis and chronic obstructive pulmonary disease, an increased activity of proteases produced by neutrophils and adhesion molecules is observed. In addition, neutrophils are an abundant source of inflammation mediators, including reactive oxidants and lipid mediators with chemotactic activity. Awareness of the increased risk of developing chronic obstructive pulmonary disease in psoriatic patients, allows to implement preventive and therapeutic actions such as smoking cessation or treatment of the inflammatory processes.